Content validity of the general nutrition knowledge questionnaire for Malaysian adult population - Mohd Rahimi, Maisarah Hazwani; Mohd 'Asri, Muhammad Rashidi; Yusuf, Rosman Kass; Ahmad Fuzi, Salma Faeza; Ab Manan, Norhafizah (Royal College of Mediceine Perak, Universiti Kuala Lumpur, 2023)
Introduction: Adequate knowledge of nutrition showed a strong association with good dietary habits and a healthy lifestyle. Nevertheless, there has not yet been a validated questionnaire on this particular topic for application among the general Malaysian populace. As such, this study was aimed to construct a questionnaire that is content validated, suitable, and developed for the Malaysian population adapted from the latest revised version of the general nutrition knowledge questionnaire (GNKQ-R) Methods: We conducted this study through one-on-one online interviews with three expert panels, to review each item of the GNKQ-R, taking into account the Malaysian Dietary Guideline 2020, and the Malaysian Adult Nutrition Survey 2014. Further, five expert panels were asked to rate the revised items based on relevance on the four-point scale Content Validity Index (CVI) was calculated for each item with a value of more than 0.8 indicating that the item is relevant to include in the questionnaire. Results: Overall, out of 47 items, five items scored CVI less than 0.8 (range 0.6- 1.0). The item on waist circumference was suggested to add by the experts. Conclusion: Five items were suggested to review or revise and one item on waist circumference is suggested to add before the questionnaire is translated to Bahasa Malaysia and further evaluated for face validity and psychometric properties.